The Effect of Digital Transformation and Digital Leadership on Talent Management Practices and Employee Performance - Suparmi Suparmi; Sri Suprapti (Jurnal Ilmiah Manajemen Kesatuan, 2026)
The rapid advancement of digital technology has encouraged organizations to enhance digital capabilities and digital leadership to optimize employee performance. This study aims to examine the influence of digital transformation and digital leadership on talent management practices and employee performance, as well as to investigate the role of talent management practices as a mediating mechanism. A quantitative approach with an explanatory research design was employed to test the causal relationships among the variables using Partial Least Squares–Structural Equation Modeling (PLS-SEM). Data were collected from 141 employee respondents in organizations that have implemented digital systems in Semarang, Surakarta, and Yogyakarta. The findings indicate that digital transformation positively affects both talent management practices and employee performance. Similarly, digital leadership positively influences talent management practices and employee performance. Furthermore, talent management practices have a positive effect on employee performance and partially mediate the relationship between digital transformation, digital leadership, and employee performance. These results highlight the critical importance of integrating digital capabilities and leadership to enhance the effectiveness of talent management practices, enabling organizations to sustainably improve employee performance through targeted talent management strategies.